Reference electrode, preparation method thereof and lithium ion semi-solid-state battery
By using polyether polymers for in-situ polymerization on the reference electrode surface, the polarization problem caused by uneven distribution of electrolytes is solved, the accuracy of battery monitoring is improved, and lithium metal is prevented from falling off in a high expansion system.
Patent Information
- Application Number
- CN202311142366.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, due to in-situ curing technology, the electrolyte distribution around the reference electrode is uneven, resulting in serious polarization, which leads to a shift in the potential of the reference electrode monitoring, affecting the accuracy of the monitoring.
Polyether polymers are used as the surface material for the reference electrodes, and homogeneous polyether in situ polymerization solid electrolytes are formed on the matrix material through in situ polymerization technology to improve interface contact and provide buffering in the high-expanding system.
The interface contact at the reference electrode is improved, polarization phenomenon is reduced, the accuracy of monitoring potential is improved, and lithium metal is prevented from falling off in a high expansion system.
Smart Images

Figure CN119627258A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a reference electrode and a preparation method thereof, and a lithium ion semi-solid battery. Background Art
[0002] Lithium-ion battery is a chemical power source. During the charge and discharge process, electrochemical reactions such as electrolyte consumption, SEI film (i.e. solid electrolyte membrane) formation, and lithium deposition at the negative electrode occur constantly inside the battery. Therefore, a method for in-situ detection of electrochemical reactions inside the battery is needed. The three-electrode method introduces a reference electrode to monitor the positive electrode potential, negative electrode potential, and impedance inside the battery in situ.
[0003] In the prior art, a more reasonable and accurate method for setting the reference electrode is to make the reference electrode from enameled wire, insert it between the diaphragm and the electrode of the lithium-ion battery cell, lead it out of the battery, and then weld it to the three-electrode tab from the outside.
[0004] CN108987836A discloses a lithium-ion battery three-electrode system and a preparation method thereof, wherein the lithium-ion battery three-electrode system comprises a battery cell and a shell, wherein the battery cell comprises a positive electrode sheet, a negative electrode sheet, a diaphragm, a reference electrode, and a short diaphragm, wherein the reference electrode is a molten lithium copper wire, wherein the diaphragm is placed between the positive electrode sheet and the negative electrode sheet, wherein the molten lithium portion of the molten lithium copper wire is inserted between the diaphragm and the negative electrode sheet, wherein the short diaphragm is placed between the molten lithium copper wire and the negative electrode sheet, wherein the positive electrode tab is welded with multiple pieces of positive electrode tabs, wherein the negative electrode tab is welded with multiple pieces of negative electrode tabs, wherein the battery cell is encapsulated in a shell, wherein the shell is filled with electrolyte. This method is applied to semi-solid batteries, because the semi-solid battery electrolyte is in a gel state after in-situ polymerization, in the absence of homogenization treatment, after the reference electrode is implanted, it is likely to cause a poor contact interface between the dissolved lithium and the electrolyte, resulting in a serious polarization phenomenon, causing large fluctuations in the potential monitored by the three electrodes, which seriously deviates from the true value, and the monitoring effect is unsatisfactory.
[0005] Therefore, it is of great significance to study and develop a reference electrode. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems in the prior art that the electrolyte around the reference electrode is unevenly distributed due to the in-situ solidification technology, resulting in serious polarization, causing the potential monitored by the reference electrode to shift, affecting the accuracy of monitoring; the problem that the reference electrode and the pole piece are in solid-solid contact, and the molten lithium is very easy to fall off in a high expansion system, resulting in poor test results and inaccurate potential after falling off; and the problem that the interface contact between the reference electrode and the electrolyte is poor due to the in-situ solidification technology, resulting in the lack of electrolyte at the reference electrode and causing unstable reference potential data. A reference electrode and a preparation method thereof, as well as a lithium ion semi-solid battery are provided. The surface of the reference electrode has a polyether polymer obtained by in-situ polymerization, which can well improve the problem of the monitored negative electrode potential deviating from the true value due to polarization, and the expansion can be buffered to a certain extent when tested in a high expansion system to avoid the shedding of lithium metal.
[0007] In order to achieve the above object, the first aspect of the present invention provides a reference electrode, wherein the reference electrode comprises a base material and a polyether polymer and a lithium salt wrapped on the base material, wherein the polyether polymer comprises a structural unit A and a structural unit B, wherein the structural unit A is derived from a monomer a shown in formula (a), the structural unit B is derived from a monomer b, and the monomer b has a molecular formula shown in formula (b);
[0008]
[0009] Wherein, R1, R2, R3 and R4 are the same or different, and are each selected from one or more of H, haloalkyl, cyano, ester, substituted or unsubstituted carboxyl;
[0010] C m H 2m O n , formula (b);
[0011] Herein, m is an integer of 2-5, and n is an integer of 1-3.
[0012] A second aspect of the present invention provides a method for preparing the aforementioned reference electrode, wherein the preparation method comprises:
[0013] (1) Mixing monomer a, monomer b and lithium salt to prepare precursor liquid A;
[0014] (2) The lithium salt cyclic ether precursor liquid A is coated on the surface of a base material to perform an in-situ polymerization reaction to obtain a reference electrode.
[0015] The third aspect of the present invention provides a lithium-ion semi-solid battery, wherein the lithium-ion semi-solid battery comprises a positive electrode plate, a separator and a negative electrode plate, a reference electrode is disposed on the surface of the negative electrode plate, and the reference electrode comprises the reference electrode described above.
[0016] Through the above technical solution, the beneficial effects of the present invention are:
[0017] (1) Since the interface of the reference electrode and the solidified electrolyte have uniform properties, there is no obvious boundary between the reference electrode and the interface of the semi-solid battery after in-situ solidification, which greatly improves the interface contact at the reference electrode. In addition, polyether electrolytes have good elasticity and can solve the problem of lithium plating falling off due to electrode expansion friction in high expansion systems.
[0018] (2) The in-situ polymerized material has an adsorption effect on the electrolyte, ensuring that there is sufficient electrolyte at the reference electrode and that the reference potential data will not be unstable due to the lack of electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic flow chart of the preparation method of the reference electrode provided by the present invention;
[0020] Figure 2 is a curve diagram of the relationship between SOC (charge capacity) and voltage of the copper wire of comparative example 1 before treatment;
[0021] Figure 3 This is a graph showing the relationship between SOC (charge capacity) and voltage after copper wire treatment in Example 1. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] As mentioned above, the first aspect of the present invention provides a reference electrode, wherein the reference electrode comprises a base material and a polyether polymer and a lithium salt wrapped on the base material, wherein the polyether polymer comprises a structural unit A and a structural unit B, wherein the structural unit A is derived from a monomer a shown in formula (a), and the structural unit B is derived from a monomer b, and the monomer b has a molecular formula shown in formula (b);
[0024]
[0025] Wherein, R1, R2, R3 and R4 are the same or different, and are each selected from one or more of H, haloalkyl, cyano, ester, substituted or unsubstituted carboxyl;
[0026] C m H 2m O n, formula (b);
[0027] Herein, m is an integer of 2-5, and n is an integer of 1-3.
[0028] In the present invention, it should be noted that a semi-solid-state battery refers to a solid-liquid hybrid battery, i.e., a lithium-ion battery in which a certain proportion of solid electrolyte is added to a liquid electrolyte in various forms (in-situ polymerization, positive electrode addition, diaphragm coating, etc.).
[0029] The inventors of the present invention have found that: since the electrolyte of a semi-solid battery is in a semi-solid gel state, if a semi-solid battery is obtained by an in-situ polymerization production method, it is more likely to cause the problem of uneven electrolyte distribution, and it is very easy to cause the electrolyte to be missing at the reference electrode during the in-situ polymerization process, resulting in poor interface contact and inaccurate reference electrode monitoring potential. However, if before the in-situ polymerization, an ether solvent is first used in the form of in-situ polymerization to perform in-situ polymerization on the base material or at the lithium-plated part of the base material to form a homogeneous polyether in-situ polymerized solid electrolyte, the problem of the monitoring potential deviating from the true value caused by polarization can be well improved, and the characteristics of the polyether solid electrolyte pre-in-situ polymerized on the base material will have a certain adsorption effect on the electrolyte, and the risk of polarization caused by insufficient electrolyte at the reference electrode can also be greatly reduced. And because of its soft nature, it will have a certain buffering effect on the expansion when tested in a high expansion system to avoid the shedding of lithium metal.
[0030] According to the present invention, preferably, the haloalkyl group is a fluoroalkyl group and / or a chloroalkyl group; more preferably, the alkyl group is a C1-C4 alkyl group; further preferably, the alkyl group is a C1-C2 alkyl group.
[0031] According to the present invention, preferably, the substituted carboxyl group is a methylcarboxyl group.
[0032] According to the present invention, more preferably, the monomer a is selected from one or more of epifluoropropane, epichlorohydrin, tetracyanoethylene oxide, 2-carboxy-oxirane acetic acid, 1,1,1-trifluoropropylene oxide, ethyl 2,3-epoxypropionate and heptafluorobutylethylene oxide.
[0033] According to the present invention, more preferably, the monomer b is selected from one or more of 1,3-dioxolane, trioxane, ethylene oxide, 1,4-dioxane, propylene oxide, tetrahydrofuran, dimethyl dioxirane, trimethylene oxide and tetrahydropyran.
[0034] According to the present invention, the matrix material is a metal wire or an electrode material, preferably a metal wire.
[0035] According to the present invention, preferably, the electrode material is selected from one or more of metallic lithium, lithium cobalt oxide and lithium iron phosphate.
[0036] According to the present invention, the material of the metal wire includes one or an alloy of two or more of gold, silver, platinum, nickel, palladium and copper.
[0037] In the present invention, it should be noted that when the base material is an electrode material, since the electrode material contains lithium, there is no need for lithium plating, lithium melting or lithium pasting. When the base material is a metal wire, lithium plating, lithium melting or lithium pasting is required. If lithium melting is used, it needs to be performed before the reference electrode is sprayed with the in-situ curing material; if lithium plating is used, it can be performed before the reference electrode is sprayed with the in-situ curing material, or it can be performed after the reference electrode is assembled into the battery; if lithium pasting is used, it needs to be performed before the reference electrode is sprayed with the in-situ curing material.
[0038] A second aspect of the present invention provides a method for preparing the aforementioned reference electrode, wherein the preparation method comprises:
[0039] (1) Mixing monomer a, monomer b and lithium salt to prepare precursor liquid A;
[0040] (2) The precursor liquid A is coated on the surface of the base material to perform an in-situ polymerization reaction to obtain a reference electrode.
[0041] According to the present invention, the two monomers, monomer a and monomer b, undergo a ring-opening polymerization reaction under appropriate reaction conditions to obtain an elastic colloidal polymer. This polyether polymer electrolyte generated by in-situ polymerization can be evenly wrapped on the copper wire, and after being introduced into the battery, it can adsorb the surrounding electrolyte during in-situ polymerization in the semi-solid battery, ensuring that the in-situ polymerization reaction around the copper wire occurs evenly, and can play a buffering and protective role for the lithium metal on the copper wire in a battery with a high expansion system.
[0042] According to the present invention, the lithium salt is LiPF6, LiAsF6, LiBF4, LiCl, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiTFSI, LiN(C4F9SO2), Li2B 12 F 12 and one or more of LiBOB, preferably LiPF6. In addition, in the present invention, when two lithium salts are selected, the molar ratio of each lithium salt is (1-10): (10-1), preferably 1:1.
[0043] According to the present invention, the conditions of the in-situ polymerization reaction include: in an environment with moisture ≤ 0.1ppm and oxygen ≤ 0.1ppm, the polymerization temperature is 50-70°C and the polymerization time is 6-24h; preferably, in an environment with moisture of 0.01-0.1ppm and oxygen of 0.01-0.1ppm, the polymerization temperature is 60-65°C and the polymerization time is 8-12h. In the present invention, if the concentration of moisture and / or oxygen is too high, it will cause water absorption problems of the material; if the temperature is too low, it will not be enough for the polymerization reaction to occur; if the temperature is too high, it will destroy the properties of the material.
[0044] According to the present invention, the molar ratio of the monomer a to the monomer b is (10-1):(1-10), preferably 1:1.
[0045] According to the present invention, the coating may be spray coating, flow coating or scraping coating. Preferably, spray coating with an atomizer bottle is adopted. In addition, the number of spraying is not limited and may be 1-5 times, preferably 1-2 times.
[0046] According to the present invention, the concentration of the lithium salt in the lithium salt cyclic ether precursor liquid A is 1-1.5 mol / L, preferably 1-1.2 mol / L.
[0047] The third aspect of the present invention provides a lithium-ion semi-solid battery, wherein the lithium-ion semi-solid battery comprises a positive electrode plate, a separator and a negative electrode plate, a reference electrode is disposed on the surface of the negative electrode plate, and the reference electrode comprises the reference electrode described above.
[0048] According to the present invention, the length of the reference electrode is 3-20 cm, and the diameter is 20-200 um; preferably, the length of the reference electrode is 5-10 cm, and the diameter is 30-50 um.
[0049] According to the present invention, the positive electrode plate includes a positive electrode current collector and a positive electrode material, wherein the positive electrode material includes NCM811 ternary material, a conductive agent and a binder, and the mass ratio of the NCM811 ternary material, the conductive agent and the binder is 97:1:2.
[0050] According to the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode material, wherein the negative electrode material includes a graphite / silicon mixed material, a conductive agent and a binder, and the mass ratio of the graphite / silicon mixed material, the conductive agent and the binder is: 98:0.5:1.5; wherein the mass ratio of graphite to silicon in the graphite / silicon mixed material is 98:2.
[0051] According to the present invention, the diaphragm is a PP / PE / PP three-layer composite polymer diaphragm.
[0052] According to the present invention, a laminated battery core pack is prepared by a battery preparation process, the battery core pack is opened to expose the negative electrode, the negative electrode located in the middle position is selected, a reference electrode is placed on a single-piece diaphragm and fixed with tape, and placed on the negative electrode sheet located in the middle position (the diaphragm separates the reference electrode and the negative electrode to prevent short circuit), the battery is reduced, the liquid to be injected is encapsulated, an in-situ polymerization precursor is prepared, monomer a and monomer b are taken as ether monomers according to the aforementioned molar ratio, lithium salt is added thereto so that the concentration of lithium salt in the ether monomer is 1-1.5 mol / L, mixed evenly and injected into the assembled battery cell, encapsulated, and soaked for 12 hours to allow the electrolyte to fully soak the electrode sheet, and then the obtained battery is heated and cured at 60°C for 12 hours to obtain a lithium ion semi-solid reference electrode battery.
[0053] In the present invention, when the base material of the reference electrode is a metal wire, it is preferred to plate the metal wire with lithium after assembling the reference electrode into the battery, and more preferably a step-by-step lithium plating method is used, i.e., the positive electrode and the negative electrode are plated with lithium respectively in three steps of small current-large current-small current.
[0054] In the present invention, after obtaining the semi-solid battery, in order to obtain a uniform and dense lithium-plated metal layer on the metal wire, the lithium plating method specifically includes:
[0055] First, lithium is plated from the positive electrode side, the positive electrode of the power supply is connected to the positive electrode of the semi-solid battery, the negative electrode of the power supply is connected to the reference electrode of the semi-solid battery, and DC charging is performed. The charging process steps are preferably charging at 5mA for 2h, charging at 10mA for 2h, and charging at 5mA for 2h; then lithium is plated from the negative electrode side, the positive electrode of the power supply is connected to the negative electrode of the semi-solid battery, the negative electrode of the power supply is connected to the reference electrode of the semi-solid battery, and DC charging is performed. The charging process steps are preferably charging at 5mA for 2h, charging at 10mA for 2h, and charging at 5mA for 2h to obtain a semi-solid battery with a reference electrode.
[0056] The present invention will be described in detail below through examples.
[0057] In the following examples, the potential parameters were measured by a battery testing system of Shenzhen Xinwei Company.
[0058] Example 1
[0059] This embodiment is intended to illustrate the preparation of a reference electrode and a lithium-ion semi-solid battery using the method of the present invention.
[0060] according to Figure 1 The schematic diagram of the process for preparing the reference electrode of the present invention is shown in Figure 1.
[0061] (1) Soak the enameled wire (copper wire) where lithium plating is required in concentrated sulfuric acid, clean it and set it aside;
[0062] (2) preparing a lithium salt cyclic ether precursor liquid A: the precursor liquid A contains an epifluoropropane monomer, a 1,3-dioxolane monomer, and a lithium salt LiPF6 in a molar ratio of 1:1, and the concentration of LiPF6 in the ether solvent is 1 mol / L;
[0063] (3) Use an atomizing bottle to evenly spray the precursor A onto the exposed copper wire, then suspend it in an oven for polymerization in an environment where the moisture and oxygen are both less than 0.1 ppm, the polymerization temperature is 60°C, the polymerization time is 12 hours, and it is taken out after the polymerization is completed. Repeat the above spraying A and polymerization twice to form a homogeneous in-situ polymerized polymer electrolyte on the copper wire to prepare a reference electrode;
[0064] (4) Prepare a laminated battery core pack through a battery preparation process, open the battery core pack to expose the negative electrode, select the negative electrode in the middle, place the reference electrode on the single-piece diaphragm and fix it with tape, and place it on the negative electrode sheet in the middle (the diaphragm separates the reference electrode and the negative electrode to prevent short circuit), reduce the battery, encapsulate the liquid to be injected, prepare an in-situ polymerization precursor, take a volume ratio of 1:1 epifluoropropane monomer and 1,3-dioxolane monomer as ether monomers, add LiPF6 thereto so that the concentration of LiPF6 in the ether monomer is 1 mol / L, mix well and inject into the assembled battery cell, encapsulate, and soak for 12 hours to allow the electrolyte to fully soak the electrode sheet, then heat and cure the obtained battery at 60°C for 12 hours to obtain a lithium-ion semi-solid-state battery without lithium plating.
[0065] (5) First, lithium is plated from the positive electrode side, the positive electrode of the power supply is connected to the positive electrode of the semi-solid battery, the negative electrode of the power supply is connected to the reference electrode of the semi-solid battery, and DC charging is performed. The charging process steps are charging at 5 mA for 2 hours, charging at 10 mA for 2 hours, and charging at 5 mA for 2 hours; then lithium is plated from the negative electrode side, the positive electrode of the power supply is connected to the negative electrode of the semi-solid battery, the negative electrode of the power supply is connected to the reference electrode of the semi-solid battery, and DC charging is performed. The charging process steps are preferably charging at 5 mA for 2 hours, charging at 10 mA for 2 hours, and charging at 5 mA for 2 hours, to obtain a lithium-ion semi-solid battery with a reference electrode.
[0066] The reference electrode of the lithium-ion semi-solid-state battery was used to monitor the negative reference potential (the potential between the negative electrode and the reference electrode) during rate charging. The experimental temperature was room temperature, and the charging rates were 0.33C, 0.5C, 1C, 1.5C, 2C, 3C and 4C, respectively. The battery was discharged after each charge with a discharge current of 0.33C. After the discharge was completed, it was left to stand for 10 minutes before the next charge.
[0067] Monitoring results such as Figure 3 As shown, Figure 3 is a curve diagram of the relationship between SOC (charge capacity) and voltage after copper wire treatment in Example 1; wherein, Figure 3The upper curve is the relationship curve between battery SOC and battery voltage at different charging rates. Figure 3 The curve below shows the relationship between battery SOC and negative parameter potential at different charging rates.
[0068] Embodiment 2-5
[0069] A reference electrode and a lithium ion semi-solid battery were prepared in the same manner as in Example 1, except that the polymerization reaction conditions of monomer a, monomer b and lithium salt were different, as shown in Table 1.
[0070] Comparative Example 1
[0071] A reference electrode and a lithium ion semi-solid reference electrode battery were prepared in the same manner as in Example 1, except that step (2) and step (3) were not performed, as shown in Table 1.
[0072] The reference electrode of the lithium ion semi-solid battery is used to monitor the negative reference potential during rate charging. The monitoring method is the same as in Example 1. The monitoring results are as follows: Figure 2 As shown, Figure 2 1 is a curve diagram showing the relationship between SOC (charge capacity) and voltage before copper wire treatment in Example 1; wherein, Figure 2 , 3 The upper curve is the relationship curve between battery SOC and battery voltage at different charging rates, and the lower curve is the relationship curve between battery SOC and negative parameter potential at different charging rates; Figure 2 As shown, the full battery voltage is normal, but the negative reference potential fluctuates at the first two rates (0.33C and 0.5C) due to interface problems. At the next several rates (1C, 1.5C, 2C, 3C, 4C), the in-situ curing is uneven, and the uneven distribution of the electrolyte leads to poor ion conduction of the reference electrode, causing the negative reference potential to drop, and the data is unreliable. Figure 3 The reference electrode pretreated by in-situ curing has an adsorption effect on the local electrolyte due to the in-situ cured polyether polymer, and its own high ionic conductivity ensures the local ion exchange of the reference electrode, resulting in a stable state for both the full battery voltage and the negative reference potential. Figure 2 and Figure 3 By comparison, it can be seen that the electrolyte of the untreated lithium-ion semi-solid battery is unevenly distributed at the untreated reference electrode due to in-situ solidification. Figure 2The negative reference potential vibrates, the polarization is large, and the test result deviates significantly from the true value. After adopting the scheme of the present invention, the reference electrode of the lithium-ion semi-solid battery can be pre-adsorbed to the electrolyte near the reference electrode after in-situ curing and encapsulation, ensuring sufficient electrolyte at the reference electrode, making the solid electrolyte formed by in-situ curing more uniform and without obvious boundaries, greatly improving the interface contact at the reference electrode, and forming good solid-liquid-solid contact with the reference electrode. Figure 3 As shown, the present invention can reduce the true value deviation caused by contact impedance and will not cause reference potential data jitter due to electrolyte loss.
[0073] Table 1
[0074]
[0075]
[0076] Test Case
[0077] The test method is to use a 1C constant current charging, stand for 10 minutes after reaching 4.2V, and a 1C constant current discharging to 2.5V and stand for 10 minutes. The cycle is unlimited until the reference electrode potential is inaccurate or fluctuates. The number of stable cycles of the reference electrodes prepared in Examples 1-5 and Comparative Example 1 is observed. The results are shown in Table 2.
[0078] Table 2
[0079] project Reference electrode stable cycles (1C / 1C cycles) Example 1 51 laps Example 2 35 laps Example 3 39 laps Example 4 27 laps Example 5 16 laps Comparative Example 1 2 laps
[0080] As shown in Table 2, the reference electrodes prepared by the method examples 1-5 of the present invention have a long number of stable cycles, indicating that the reference electrode of the present invention can effectively extend the cycle life of the reference electrode battery. The length of the cycle life of the reference electrode can indirectly characterize the degree of close bonding between the metallic lithium and the copper wire, because if the metallic lithium falls off, the monitored negative electrode potential will fluctuate or jitter, the polarization will be large, and the test result will obviously deviate from the true value.
[0081] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A reference electrode, characterized in that The reference electrode comprises a base material, a polyether polymer and a lithium salt wrapped on the base material, wherein the polyether polymer comprises a structural unit A and a structural unit B, wherein the structural unit A is derived from a monomer a shown in formula (a), and the structural unit B is derived from a monomer b, and the monomer b has a molecular formula shown in formula (b); Wherein, R1, R2, R3 and R4 are the same or different, and are each selected from one or more of H, haloalkyl, cyano, ester, substituted or unsubstituted carboxyl; C m H 2m O n , formula (b); Herein, m is an integer of 2-5, and n is an integer of 1-3.
2. The reference electrode according to claim 1, wherein The haloalkyl group is a fluoroalkyl group and / or a chloroalkyl group; Preferably, the alkyl group is a C1-C4 alkyl group, more preferably a C1-C2 alkyl group. And / or, the substituted carboxyl group is a methylcarboxyl group.
3. The reference electrode according to claim 1, wherein The monomer a is selected from one or more of epifluoropropane, epichlorohydrin, tetracyanoethylene oxide, 2-carboxy-oxirane acetic acid, 1,1,1-trifluoropropylene oxide, ethyl 2,3-epoxypropionate and heptafluorobutylethylene oxide.
4. The reference electrode according to claim 1, wherein The monomer b is selected from one or more of 1,3-dioxolane, trioxane, ethylene oxide, 1,4-dioxane, propylene oxide, tetrahydrofuran, dimethyl dioxirane, trimethylene oxide and tetrahydropyran.
5. The reference electrode according to any one of claims 1 to 4, wherein The matrix material is a metal wire or an electrode material; Preferably, the matrix material is a metal wire, and the metal wire is subjected to lithium plating, lithium melting or lithium pasting treatment; And / or, the material of the metal wire includes one or an alloy of two or more of gold, silver, platinum, nickel, palladium and copper; And / or, the electrode material is selected from one or more of metallic lithium, lithium cobalt oxide and lithium iron phosphate.
6. A method for preparing a reference electrode according to any one of claims 1 to 5, characterized in that: The preparation method comprises: (1) Mixing monomer a, monomer b and lithium salt to prepare precursor liquid A; (2) The precursor liquid A is coated on the surface of the base material to perform an in-situ polymerization reaction to obtain a reference electrode.
7. The preparation method according to claim 6, wherein: The lithium salt is LiPF6, LiAsF6, LiBF4, LiCl, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiTFSI, LiN(C4F9SO2), Li2B 12 F 12 and one or more of LiBOB, preferably LiPF6.
8. The preparation method according to claim 6, wherein: The conditions of the in-situ polymerization reaction include: in an environment with moisture ≤ 0.1 ppm and oxygen ≤ 0.1 ppm, the polymerization temperature is 50-70° C., and the polymerization time is 6-24 h; Preferably, in an environment with a moisture content of 0.01-0.1 ppm and an oxygen content of 0.01-0.1 ppm, the polymerization temperature is 60-65° C. and the polymerization time is 8-12 h.
9. The preparation method according to claim 6, wherein: The molar ratio of the monomer a to the monomer b is (10-1): (1-10); And / or, the concentration of the lithium salt in the precursor liquid A is 1-1.5 mol / L.
10. A lithium ion semi-solid battery, characterized in that: The lithium-ion semi-solid battery comprises a positive electrode sheet, a separator and a negative electrode sheet. A reference electrode is disposed on the surface of the negative electrode sheet. The reference electrode comprises the reference electrode described in any one of claims 1 to 6.
11. The lithium-ion semi-solid battery according to claim 10, wherein: The reference electrode has a length of 3-20 cm and a diameter of 20-200 um; Preferably, the reference electrode has a length of 5-10 cm and a diameter of 30-50 um.
Citation Information
Patent Citations
A lithium ion battery three-electrode system and a preparation method thereof
CN108987836A
Cited By
Three-electrode battery, reference electrode, preparation method of reference electrode and electric device
CN120109316A
Three - electrode battery, reference electrode and its preparation method, and electrical device
CN120109316B